PERKAWINAN BEDA AGAMA DI INDONESIA - Abdul Kholiq (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Marriage is a part of human life on this earth, and in Indonesia live many human diverse religions recognized by the government, so that in everyday life they are interacting with each other and sometimes will lead to marriage among those who different religions, this would cause problems and the validity of the marriage, therefore, in order not to cause problems and legitimate marriage according to the religion and the government, then the marriage should be according to their religion and the laws of marriage in force, namely Law No. 1 of 1974.